Spatial concentration and variability of rainfall in the Iguaçu River Basin, State of Paraná−Brazil - de Andrade, Aparecido Ribeiro (2023)
The analysis of rainfall as an environmental factor that influences landscape dynamics is an important and ongoing topic of discussion. This discussion can be centred on the discovery of impacts caused by the increase or decrease in rainfall frequency and intensity. From this perspective, this study sought to analyse the rainfall variability in the Iguaçu River basin, located in the State of Paraná, southern Brazil. The main objective was focused on the temporal-spatial rainfall distribution in the study area and its interaction with landscape dynamics (different land uses). Precipitation data for the period 1988−2018 were obtained from the ‘Águas Paraná’ Institute. To calculate the Concentration Index−CI values of the study area, data analysis was performed using the ‘R’ software with Climatol and Precindicon subroutines of the software, and analysis of Landsat 8 satellite images through ArcGIS. The results indicated that there was a well-defined spatial variability in the study area, as the CIs defined higher rainfall concentrations upstream from the river basin and lower rainfall concentrations downstream—implying that these processes may be strongly associated with land use.